Long-term Outcomes After Liver Transplantation Among Human Immunodeficiency Virus–Infected Recipients. Issue 1 (January 2016) - Locke, Jayme E.; Durand, Christine; Reed, Rhiannon D.; MacLennan, Paul A.; Mehta, Shikha; Massie, Allan; Nellore, Anoma; DuBay, Derek; Segev, Dorry L.
Abstract : Background: Early outcomes after human immunodeficiency virus (HIV) + liver transplantation (LT) are encouraging, but data are lacking regarding long-term outcomes and comparisons with matched HIV− patients. Methods: We examined outcomes among 180 HIV+ LT, and compared outcomes to matched HIV− counterfactuals (Scientific Registry of Transplant Recipients 2002-2011). Iterative expanding radius matching (1:10) on recipient age, race, body mass index, hepatitis C virus (HCV), model for end-stage liver disease score, and acute rejection; and donor age and race, cold ischemia time, and year of transplant. Patient survival and graft survival were estimated using Kaplan-Meier methodology and compared using log-rank and Cox proportional hazards. Subgroup analyses were performed by transplant era (early: 2002-2007 vs modern: 2008-2011) and HCV infection status. Results: Compared to matched HIV− controls, HIV+ LT recipients had a 1.68-fold increased risk for death (adjusted hazard ratio [aHR], 1.68, 95% confidence interval [95% CI], 1.28-2.20; P < 0.001), and a 1.70-fold increased risk for graft loss (aHR, 1.70; 95% CI, 1.31-2.20; P < 0.001). These differences persisted independent of HCV infection status. However, in the modern transplant era risk for death (aHR, 1.11; 95% CI, 0.52-2.35; P = 0.79) and graft loss (aHR, 0.89; 95% CI, 0.42-1.88; P = 0.77) were similar between monoinfected and uninfected LT recipients. In contrast, independent of transplant era, coinfected LT recipients had increased risk for death (aHR, 2.24; 95% CI, 1.43-3.53; P < 0.001) and graft loss (aHR, 2.07; 95% CI, 1.33-3.22; P = 0.001) compared to HCV+ alone LT recipients. Conclusions: These results suggest that outcomes among monoinfected HIV+ LT recipients have improved over time. However, outcomes among HIV+ LT recipients coinfected with HCV remain concerning and motivate future survival benefit studies. Abstract : Risk for death and graft loss were similar between HIV+ monoinfected and uninfected liver transplant recipients. In contrast, independent of transplant era, HIV+/HCV+ coinfected liver transplant recipients had increased risk for death and graft loss compared to HCV+ alone liver transplant recipients.